Penerapan Pendekatan Saintifik Untuk Meningkatkan Hasil Belajar IPA - Riniwanti Hamang; Andi Makkasau (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2024)
The problem of this research is motivated by the low learning outcomes of students in science. This is because the conventional learning process is more centered on the teacher. The formulation of the problem in this research is "how the application of a scientific approach can improve the science learning outcomes of fifth grade students of SDN 14 Samanggi. This type of research is Classroom Action Research (CAR) which consists of 2 cycles. Each cycle consists of 4 stages, namely planning, implementation of observation, and reflection. The data in this study were obtained from teachers and students through observation, learning outcomes tests and document observations. Based on the results of the reflection carried out in the first cycle, it is known that only a small number of students can achieve the indicators of success, the results of the reflection in the second cycle show that most of the students have achieved the indicators of success for the same material as the first cycle. While the results of the reflection in the second cycle obtained data that students who achieve success indicators have increased compared to the first cycle for different materials. The conclusion is that the application of a scientific approach can improve student learning outcomes in science class V SDN 14 Samanggi, Simbang district, Maros district.